(3GdhLjR aj GdeGdjI GdYGeI (B/s - (3fGTQ, ShRj YOdfjs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2000)
(3fXQjGJ GdfabGJ GdYGeI ,JYQja GdfabI GdYGeI ,JbSje GdfabI GdYGeI ,bhGYO GdEfaGb ,fXQjI GdEOGQGJ GdYGeI ,GdJYQja HGdEjQGOGJ GdYGeI hJbSjeGJgG GdeNJdaI ,GjQGOGJ GdOhdI GdEbJUGOjI,fXQjI GdVQjHI ,GdbQhV GdYGeI ,GdejRGfjI ,EYOGO GdejRGfjI GYJeGO GdejRGfjI ,JfajP GdejRGfjIs
Keywords: (3GdEjQGOGJ GdYGeIs; (3GdejRGfjI GdYGeIs; (3GdfabGJ GdYGeIs